The Effects of Noninvasive Vagus Nerve Stimulation on Fatigue and Immune Responses in Patients With Primary Sjögren's Syndrome. Issue 5 (17th October 2018) - Tarn, Jessica; Legg, Sarah; Mitchell, Sheryl; Simon, Bruce; Ng, Wan‐Fai
Abstract : Objectives: Primary Sjögren's syndrome (pSS) sufferers have rated chronic fatigue as the most important symptom needing improvement. Emerging data suggest that stimulation of the vagus nerve can modulate immunological responses. The gammaCore device (electroCore), developed to stimulate the cervical vagus nerve noninvasively, was used to assess the effects of vagus nerve activation on immune responses and clinical symptoms of pSS. Materials and Methods: Fifteen female pSS subjects used the nVNS device twice daily a 26‐day period. At baseline, blood was drawn before and after application of the gammaCore device for 90 sec over each carotid artery. The following fatigue‐related outcome measures were collected at baseline, day 7 and day 28: EULAR patient reported outcome index, profile of fatigue (Pro‐F), visual analogue scale of abnormal fatigue, and Epworth sleepiness scale (ESS). Whole blood samples were stimulated with 2 ng/mL lipopolysaccharide (LPS) and the supernatant levels of IFNγ, IL12‐p70, TNFα, MIP‐1α, IFNα, IL‐10, IL‐1β, IL‐6, and IP‐10 were measured at 24 hours. In addition, clinical hematology and flow cytometric profiles of whole blood immune cells were analyzed. Results: Pro‐F and ESS scores were significantly reduced across all three visits. LPS‐stimulated production of IL‐6, IL‐1β, IP‐10, MIP‐1α, and TNFα were significantly reduced over the study period. Patterns of NK‐ and T‐cell subsets also altered significantly over the study period. Interestingly, lymphocyte counts at baseline visit correlated to the reduction in fatigue score. Conclusion: The vagus nerve may play a role in the regulation of fatigue and immune responses in pSS and nVNS may reduce clinical symptoms of fatigue and sleepiness. However, a sham‐controlled follow‐up study with a larger sample size is required to confirm the findings.